2019
DOI: 10.2196/13327
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Maximal Oxygen Uptake From Daily Activity Data Measured by a Watch-Type Fitness Tracker: Cross-Sectional Study

Abstract: Background Cardiorespiratory fitness (CRF), an important index of physical fitness, is the ability to inhale and provide oxygen to the exercising muscle. However, despite its importance, the current gold standard for measuring CRF is impractical, requiring maximal exercise from the participants. Objective This study aimed to develop a convenient and practical estimation model for CRF using data collected from daily life with a wristwatch-type device. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…These percentages increased by 11-16% following to addition of the PA score obtained using the questionnaire in the model (Table 4) These SEE values can be replaced with %SEE values of 10.8-11.2%. Other types of VO 2max estimation studies reported %SEE values of 11.4% in the 20-m shuttle run test study [26] and 10-15% in wearable device studies [13,27,28]. The SEE values in the present study seem to be favorable when compared with those calculated in other VO 2max prediction studies.…”
Section: Discussionsupporting
confidence: 58%
“…These percentages increased by 11-16% following to addition of the PA score obtained using the questionnaire in the model (Table 4) These SEE values can be replaced with %SEE values of 10.8-11.2%. Other types of VO 2max estimation studies reported %SEE values of 11.4% in the 20-m shuttle run test study [26] and 10-15% in wearable device studies [13,27,28]. The SEE values in the present study seem to be favorable when compared with those calculated in other VO 2max prediction studies.…”
Section: Discussionsupporting
confidence: 58%
“…The resulting regression equation showed a good correlation between estimated and measured V O 2max (r ϭ 0.85), and the standard error of the estimate was 14% (437 mL O 2 /min). A similar approach was presented in a recent report (16) showing how daily energy expenditure and HR could be combined with anthropometric variables to predict V O 2max as derived by submaximal tests. The main disadvantage of those methods using free-living data to generate a fitness index from wearable sensor data is the high bias toward sedentary data, which is abundant during the monitoring period.…”
Section: Discussionmentioning
confidence: 94%
“…There are a number of validated tests including the 6-minute walk test, 18 activity monitors 19 and the resting heart rate method 20 that can be used to give an estimate of a patient's VO 2 max. All three methods can be performed remotely, be self administered 19,20 or in the case of resting heart rate be extracted from existing data in healthcare records. This would allow clinicians to remotely assess patients' exercise capacity at home, without any additional burden in clinic time.…”
Section: How Could We Practically Test Exercise Capacity On a Large Smentioning
confidence: 99%